Adsorption Properties of Basic Dyes (Maxilon Red GRL and Maxilon Yellow GRL) onto Bentonite - Koyuncu, Menderes (Asian Journal of Chemistry, 2010)
In this study, adsorption kinetics, thermodynamics and adsorption stability parameters of maxilon red GRL and maxilon yelow GRL which are used in textile industry especially in dyeing of acrylic fibers on to bentonite were studied. The adsorption of the dyes onto bentonite was investigated during a series of batch adsorption experiments to determine the effect of initial dye concentration and contact time. The Langmuir and Freundlich isotherm models were tested for their applicability. Adsorption capacities, adsorption stability constants and Langmuir and Freundlich constants were calculated. Kinetic studies have been made at two different temperatures Adsorption equilibrium studies have been studied using 5 different dye solutions at 37 ºC, pH 4.5-5.0 and in 10 h. The experimental data were analyzed using the pseudo first-order adsorption kinetic model. According to this model, the rate constants were evaluated at two different temperatures.